Vascular dysfunction—The disregarded partner of Alzheimer's disease. Issue 1 (1st January 2019) - Sweeney, Melanie D.; Montagne, Axel; Sagare, Abhay P.; Nation, Daniel A.; Schneider, Lon S.; Chui, Helena C.; Harrington, Michael G.; Pa, Judy; Law, Meng; Wang, Danny J. J.; Jacobs, Russell E.; Doubal, Fergus N.; et al.
Abstract: Increasing evidence recognizes Alzheimer's disease (AD) as a multifactorial and heterogeneous disease with multiple contributors to its pathophysiology, including vascular dysfunction. The recently updated AD Research Framework put forth by the National Institute on Aging–Alzheimer's Association describes a biomarker‐based pathologic definition of AD focused on amyloid, tau, and neuronal injury. In response to this article, here we first discussed evidence that vascular dysfunction is an important early event in AD pathophysiology. Next, we examined various imaging sequences that could be easily implemented to evaluate different types of vascular dysfunction associated with, and/or contributing to, AD pathophysiology, including changes in blood‐brain barrier integrity and cerebral blood flow. Vascular imaging biomarkers of small vessel disease of the brain, which is responsible for >50% of dementia worldwide, including AD, are already established, well characterized, and easy to recognize. We suggest that these vascular biomarkers should be incorporated into the AD Research Framework to gain a better understanding of AD pathophysiology and aid in treatment efforts.